Streptococcus mutans adhesion and releasing of metallic ions in dental alloys - Zavanelli, Adriana Cristina [UNESP]|Zavanelli, Ricardo Alexandre; Mazaro, José Vitor Quinelli [UNESP]; Falcón-antenucci, Rosse Mary [UNESP] (Faculdade de Odontologia de Piracicaba - UNICAMP, 2015)
AIM: To evaluate the adherence of Streptococcus mutans to the surface of the amalgam and copper/aluminum alloy samples and also evaluate the release of metallic ions. METHODS: The prepared medium was changed every 72 h and analyzed by atomic absorption spectrophotometer. Samples were removed from the prepared medium at 15, 30, 48 and 60 days. RESULTS: The result shows that ions released were statistically different among all groups, and so were both biofilm and pits formation and the corrosion induced by the S. mutans in both types of samples. SEM observation of the samples immersed in the prepared medium with S. mutans showed adherence of microorganisms on the whole surface, in all groups. CONCLUSIONS: The S. mutans adhere to both amalgam and copper/aluminum alloy causing corrosion of those restorations. S. mutans produced a greater ions release in Cu/Al alloy; in amalgam, the ions release was not influenced by exposure to S. mutans.
Keywords: Dental alloys; Corrosion; Ions